The Impact of the University Education (Research) index on the Global Competitiveness of the United Arab Emirates During the Period (2021-2022) - Mahdi, Shawk Hasan (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed to demonstrate the relationship of the university education index (research) to the global competitiveness of the United Arab Emirates. The study relied on the quantitative approach to data analysis. The study sample consisted of a group of (manager, executive director, head of department/division, employee) who work in the departments, departments and offices of quality management and academic accreditation in accredited higher education institutions, the sample size was (360) individuals. The sample size was calculated to find the number of its individuals based on the equation for determining the size of the statistical sample for an unknown statistical population at the level (0.05), where (360) were distributed) A questionnaire was collected on the study sample, and (340) were retrieved. After examining the questionnaires, (330) questionnaires were found valid for analysis at a rate of (91.6%), and the hypotheses were tested using appropriate statistical methods from the Statistical Package for the Social Sciences (SPSS). The study reached several results, the most important of which is that there is a statistically significant effect at a significant level (0.05 ≥ α) for research on competitiveness, represented by its combined dimensions, for the United Arab Emirates, and the relationship between the two variables was positive. This explains that the research dimension positively affects the dependent variable, competitiveness, which is represented by its combined dimensions. Therefore, it was recommended that universities should commit to processes of developing and improving the quality of their outputs. Encouraging universities to provide distinguished information management systems through the use of technology in administrative work.